'Popper'‐induced vision loss. (19th February 2013) - Krilis, Matthew; Thompson, Julia; Atik, Alp; Lusthaus, Jed; Jankelowitz, Stacey
Abstract Amyl nitrite 'poppers' are recreational drugs, which are a potent source of nitric oxide. The use of 'poppers' can cause psychoactive stimulation, reduced blood pressure, tachycardia and involuntary muscle relaxation. Their use is becoming increasingly common around the world, including approximately 60% of Australia's male homosexual community. We report the first case of 'popper'‐induced vision loss in Australasia.